A Suction Trap for Sampling Aphids and Aphidophagous Insects in Pecan Trees - Dutcher, James D (International Research Journal of Insect Sciences, 2016)
Aphids and aphidophagous insects were monitored in a pecan orchard by enumerating the insects collected on leaf samples and suction trap samples. Season long monitoring of the pecan foliage revealed that the aphid abundance prior to the late season outbreak on the leaves increased to higher population levels than could not be explained by the reproductive potential of the aphids. Concomitant season long sampling of the air in the canopy indicated that fecund alate aphids were continuously abundant in the air both before and between the outbreaks on the leaves. The results have important implications for improving scouting methods to predict aphid outbreaks and facilitate insecticide applications for aphid control.